Seroprevalencia de micosis pulmonares en pacientes con sintomatología de enfermedad respiratoria crónica baja. Alto Huallaga, Perú 2004 - Gómez, Walter (2006)
Objective: To detect lung mycosis (Paracoccidioides brasiliensis, Aspergillus sp., and Histoplasma capsulatum) with chronic respiratory disease symptoms (Huanuco and San Martin departments forest). Design: Cross-sectional study. Setting: Peru's Alto Huallaga . Patients: Study done in six districts' (Rupa Rupa, Tocache, Uchiza, Santa Lucia, Aucayacu and Puerto Inca - Sungaro) subjects with diagnosis of chronic respiratory disease, three or more episodes of bronchitis per year and/or cough for over three months in whom pulmonary tuberculosis was screened by direct baciloscopy. Interventions: Each subject had a clinical epidemiological card filled and 10 mL of blood was collected for immunodiffusion test for Histoplasma capsulatum, Paraccocidiodes brasiliensis, and Aspergilus sp, between April and September 2004. Main outcome mesasures: Mycosis seroprevalence, including Histoplasma capsulatum, Aspergilus spp., and Paracoccidioides brasiliensis Results: From 640 cases, 327 (51,1%) were males, avegare age 37,1 years and time of disease 7,4 months. Mycosis seroprevalence was 1,7% (11/640), including 4 Histoplasma capsulatum and 7 Aspergilus spp. No positive cases of Paracoccidioides brasiliensis was obtained and the positive cases were associated only to 'low weight' (p = 0,004). Conclusion: Although the mycosis serologic frequency was low, we suggest to consider mycosis in the differential diagnosis of cases with chronic respiratory diseases in endemic zones, as well as the use of immunodiffusion techniques for diagnosis.